LIFE SAFETY AND RATIONAL AND SAFE USE OF MEDICINES - I. Yu. Nefedov; I. Yu. Nefedova; E. M. Salimgareeva; N. V. Chibrikova; Z. O. Sycheva; A. O. Myazina; A. V. Sharavatova; A. S. Samorukova (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье)
Drugs are an integral part of modern civilization, accompanying a person from conception to death, ensuring prevention and treatment of diseases, health, and a comfortable life. The expansion of the medicine market, possibility of drug remote purchase and delivery actualize the problem of safe and rational use of medicines and make it an integral part of safe human life. Public education about medicines is one of the main activities of the WHO to promote their rational use. To make the educational activity of pharmacists more effective, it is necessary to explore the awareness of the population on pharmaceuticals. In this study, performed with the involvement of students, we found that about 70% of respondents consider it necessary to deliver medicines from a pharmacy to their home; however, approximately 40% of respondents do not know the difference between traditional (allopathic) medicines and homoeopathic medicines and some 30% of respondents do not know their difference from dietary supplements. More than half of respondents do not know about long-release drugs, while 30% of people mistakenly believe that conventional tablets last longer. Almost half of respondents using homeopathic drugs noticed no positive effect from them; among people taking dietary supplements, only 15% reported positive effects. This raises the question of the rationality of their use by this population group. Approximately 70% of respondents believed that traditional medications were more effective than homeopathic ones; still about 60–70% of respondents would like to know more about long-release tablets, homeopathic medications, and dietary supplements. In general, our findings indicate insufficient public awareness of medicines and the need for educational programs to ensure their rational and safe use.